AB0592 A Study of Short Term Progression of Takayasu Arteritis. (10th June 2014) - Joshi, P.N.; Parikh, T.; Sharma, V.; Yathish, G.C.; Doshi, B.; Samant, R.; Mangat, G.; Balakrishnan, C.; Amin, S.; Joshi, V.
Abstract : Background: Takayasu arteritis (TA) is a rare large vessel vasculitis predominantly affecting young females in Indian subcontinent. Objectives: To know predictive factors for progression of Takayasy arteritis. Methods: Retrospective proforma based analysis of all patients diagnosed with TA with minimum two year followup and followup imagining at two centersfrom 2007-2012 was performed. Results: Data of 42 patients was available [31 (73.81%) females and 11 (26.19%) males] with mean age of 32.7±12.6 (16-54) years. Mean delay in diagnosis 2.9±2.2 (0.25-10) years.Absent peripheral pulse and arterial bruits were present in 24 (57.14%) and 33 (78.57%) patients respectively. 5 (11.90%) patients diagnosed in prepulseless stage with pyrexia of unknown origin (PUO) with high ESR. Mean ESR 63±29 mm/hr (8-135) and mean CRP 28±22 mg/dl (4-90). All treated with steroidsand immunosuppressants by treating physician. New onset arterial bruit or loss of pulse was found in 16 (38%) and 7 (16.66%)patients respectively. (Table-1 )Of the 5 patients who presented in prepulseless stage, 2 had no further progression.At 2 year follow up mean ESR (p=0.03) and mean CRP (p=0.01) were associated with new onset pulse loss. Conclusions: Patients with persistently high ESR and CRP were more prone for new onset arterial bruit or loss of palpable pulse. References: Misra R, Danda D, Rajappa SM, Ghosh A, Gupta R, Mahendranath KM, Jeyaseelan L, Lawrence A, Bacon PA; Indian Rheumatology Vasculitis (IRAVAS) group. Devlopment and initial validation of the Indian Takayasu Clinical Activity Score (ITAS 2010).Rheumatology (Oxford). 2013 Oct;52(10):1795-801 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6087